Prinsip Kepastian Hukum Pengesahan Perjanjian Perkawinan Oleh Notaris Pasca Putusan Mahkamah Konstitusi RI Nomor 69/PUU/XIII/2015 - Anas, Fitria; Tanuwijaya, Fanny; Efendi, Aan (UNES Law Review, 2023)
The Constitutional Court's involvement of the notary profession in approving marriage agreements without the support of technical regulations regarding the legal mechanism of such agreements has led to normative conflicts, created legal uncertainties, and has the potential to harm husbands and wives who enter into marriage agreements. This situation involves informal changes in legislation and the absence of legal provisions regulating the notary's authority. The issues arising include juridical aspects related to the notary's authority, legal certainty issues, and sociological aspects related to the legality of marriage agreements not recognized by notaries. In this context, this research aims to examine whether the notary's authority to approve marriage agreements, as per the Constitutional Court Decision, is not contrary to the principle of legal certainty and how the understanding of the meaning of marriage agreements for objects other than marital property. The research findings indicate that the new authority granted by the Constitutional Court Decision No. 69/PUU/XII/2015 is an attribution-based authority derived from legislation. In other words, notaries obtain authority directly from the wording of Article 29 paragraph (1) of the Marriage Law. Article 29 paragraph (1) of the Marriage Law after the Constitutional Court Decision No. 69/PUU/XII/2015 stipulates that marriage agreements can be made before, during, and throughout the marriage with a written agreement certified by the Marriage Registrar or Notary. Although marriage agreements with objects other than marital property are not explicitly regulated, they are implicitly addressed, essentially governing family relationships. The existence of marriage agreements with objects other than marital property aims to protect and provide benefits to the parties involved in case of disputes.